2015
DOI: 10.1002/env.2331
|View full text |Cite
|
Sign up to set email alerts
|

Restricted spatial regression in practice: geostatistical models, confounding, and robustness under model misspecification

Abstract: In spatial generalized linear mixed models (SGLMMs), covariates that are spatially smooth are often collinear with spatially smooth random effects. This phenomenon is known as spatial confounding and has been studied primarily in the case where the spatial support of the process being studied is discrete (e.g., areal spatial data). In this case, the most common approach suggested is restricted spatial regression (RSR) in which the spatial random effects are constrained to be orthogonal to the fixed effects. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(182 citation statements)
references
References 30 publications
10
171
0
1
Order By: Relevance
“…Murakami and Griffith () demonstrated that, in the presence of such spatial process, the use of E ⊥ leads to a severe overestimation of the statistical significance of the coefficients. Hanks, Schliep, Hooten, and Hoeting () obtained similar results through simulations under misspecification.…”
Section: Spatial Extension Of the Uqrmentioning
confidence: 59%
“…Murakami and Griffith () demonstrated that, in the presence of such spatial process, the use of E ⊥ leads to a severe overestimation of the statistical significance of the coefficients. Hanks, Schliep, Hooten, and Hoeting () obtained similar results through simulations under misspecification.…”
Section: Spatial Extension Of the Uqrmentioning
confidence: 59%
“…() and Hanks et al. (). Heuristically, our Kα serves as an autocovariate relating a site to the occupancy status of its neighbors.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial confounding and related identifiability issues are also challenging topics in spatial models (Hodges and Reich 2010). Spatial confounding has primarily been discussed for areal spatial data (e.g., Paciorek 2010), however, recently (Hanks et al 2015) studied spatial confounding for geostatistical H processes (i.e., continuous spatial support). Multivariate spatial and spatiotemporal models as well as nonlinear dynamical spatiotemporal models (e.g., Wikle and Hooten 2010) are active areas of research.…”
Section: Future Directionsmentioning
confidence: 99%
“…Traditional likelihoodbased approaches to modeling have allowed for scientifically meaningful data structures, though, in complicated situations with heavily parameterized models and limited or missing data; estimation by likelihood maximization is often problematic or infeasible. Developments in numerical approximation methods have been useful in many cases, especially for highdimensional parameter spaces (e.g., NewtonRaphson and E-M methods, Givens and Hoeting 2005), though can still be difficult or impossible to implement and have no provision for accommodating uncertainty at multiple levels.…”
Section: Hierarchical Modelsmentioning
confidence: 99%